No paradise yet the world's women face the new century (London Panos, 2000)
Extrait de la couverture : "The women's movement was probably the most influential social phenomenon of the last quarter of the 20th century. Many governments were forced to respond to its calls for change. Yet, at the beginning of the 21th century, m illions of women worldwide are still denied the most fundamental rights. In this book, 12 journalists from Africa, Asia and Latin America investigate struggles to reform punitive personal status laws, to introduce fair marriage contracts, to allow divorced women child custody rights and independent access to land, to end sexual harassment in education, discriminatory employment practices and domestic violence. A unique aspect of this book is tis holistc approach. In each chapter, the particular issue under scrutiny is laso examined from the persepectice of its effect on women's reproductive rights and health - still the area of women's experience over which societies exercise the most rigid, though often hidden, control."
Keywords: Femmes -- Conditions sociales